The reluctant empress - Hamann, Brigitte, 1940-2016 (Ullstein, 1996)
She was the romantic idol of her age, the extraordinarily beautiful and mysterious Empress Elisabeth of Austria whose exploits made her a legend in nineteenth-century Europe and beyond. This biography by Brigitte Hamann reveals the truth of a complex and touching, curiously modern personality, her refusals to conform, escaping to a life of her own, filled with literature, ideas and the new political passions of the age.